Alpha-synuclein misfolding as fluid biomarker for Parkinson’s disease measured with the iRS platform - Martin Schuler; Grischa Gerwert; Marvin Mann; Nathalie Woitzik; Lennart Langenhoff; Diana Hubert; Deniz Duman; Adrian Höveler; Sandy Galkowski; Jonas Simon; Robin Denz; Sandrina Weber; et al. (EMBO Molecular Medicine)
Abstract Misfolding and aggregation of alpha-synuclein (αSyn) play a key role in the pathophysiology of Parkinson’s disease (PD). Despite considerable advances in diagnostics, an early and differential diagnosis of PD still represents a major challenge. We innovated the immuno-infrared sensor (iRS) platform for measuring αSyn misfolding. We analyzed cerebrospinal fluid (CSF) from two cohorts comprising PD cases, atypical Parkinsonian disorders, and disease controls. We obtained an AUC of 0.90 (n = 134, 95% CI 0.85–0.96) for separating PD/MSA from controls by determination of the αSyn misfolding by iRS. Using two thresholds divided individuals as unaffected/affected by misfolding with an intermediate area in between. Comparing the affected/unaffected cases, controls versus PD/MSA cases were classified with 97% sensitivity and 92% specificity. The spectral data revealed misfolding from an α-helical/random-coil αSyn in controls to β-sheet enriched αSyn in PD and MSA cases. Moreover, a first subgroup analysis implied the potential for patient stratification in clinically overlapping cases. The iRS, directly measuring all αSyn conformers, is complementary to the αSyn seed-amplification assays (SAAs), which however only amplify seeding competent conformers.